2005
DOI: 10.1007/s11010-005-8234-z
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated deficit of mitochondrial oxidative phosphorylation in skeletal muscle: Role of carnitine and lipoic acid

Abstract: Mitochondrial damage has implicated a major contributor for ageing process. In the present study, we measured mitochondrial membrane swelling, mitochondrial respiration (state 3 and 4) by using oxygen electrode in skeletal muscle of young (3-4 months old) and aged rats (above 24 months old) with supplementation of L: -carnitine and DL: -alpha-lipoic acid. Our results shows that the mitochondrial membrane swelling and state 4 respiration were increased more in skeletal muscle mitochondria of aged rats than in y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 29 publications
2
26
1
1
Order By: Relevance
“…In these articles, the coefficients of variation [CVs; CVϭ100ϫ(sd/ mean)], calculated from data presented in data tables, appeared to be similar regardless of the treatment group or variable being measured. Subsequently, we observed a similar effect in a published article from the same investigator (1).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…In these articles, the coefficients of variation [CVs; CVϭ100ϫ(sd/ mean)], calculated from data presented in data tables, appeared to be similar regardless of the treatment group or variable being measured. Subsequently, we observed a similar effect in a published article from the same investigator (1).…”
supporting
confidence: 70%
“…Outcome measures are as listed below. A) Kumaran et al (1): results are for skeletal muscle mitochondria isolated from young and old rats treated with l-carnitine and dl-␣-lipoic acid. Substrates were succinate, ␤-hydroxybutryate, glutamate, glutamate ϩ malate, and pyruvate ϩ malate.…”
Section: Discussionmentioning
confidence: 99%
“…Results from a limited number of small scale studies suggest that carnitine supplementation might confer insulin sensitizing actions in glucose intolerant or diabetic humans [16,58,72]. The precise mechanisms underlying the benefits of supplemental l -carnitine remain unclear, although mitochondrial energy metabolism and redox state have been suggested as probable targets [2,5,67,97]. Thus, by buffering intramitochondrial imbalances between acyl-CoA load and TCA cycle activity, this nutrient might play a critical role in combating the damaging effects of nutrient surplus.…”
Section: Carnitine As An Antilipotoxic Therapymentioning
confidence: 99%
“…ALCA, together with alpha-lipoic acid, was shown to improve mitochondrial energy metabolism and decrease oxidative stress leading to improved memory in aged rats [144,145]. Several studies have reported that supplementing rats with both L -carnitine and alpha-lipoic acid halts age-related increases in reactive oxygen species (ROS), lipid peroxidation, protein carbonylation, and DNA strand breaks in heart, skeletal muscle and brain, concomitant with improvement in mitochondrial enzyme and respiratory chain activities [146-149]. In a clinical trial of Levocarnitine-treated elderly patients [150], there was significant improvement in total fat mass, total muscle mass, total cholesterol, LDL-C, HDL-C, triglycerides, apoA1, and apoB with concomitant decreases in physical and mental fatigue.…”
Section: Introductionmentioning
confidence: 99%